2017
DOI: 10.1177/1074248416687874
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning in Cardiovascular Surgery

Abstract: The existing clinical studies on remote ischemic preconditioning in patients undergoing cardiovascular surgery are critically reviewed, with a focus on infarct size reduction and clinical outcome as end points. Confounders, notably the use of propofol anesthesia are identified. The need for better designed trials with a more targeted approach is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
0
15
1
2
Order By: Relevance
“…Anesthesia is a confounder of cardioprotection by RIPC [85]. A meta-analysis by Zangrillo and colleagues reported that volatile anesthesia combined with RIPC reduced the post-operative mortality rate in patients undergoing cardiac surgery [86].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia is a confounder of cardioprotection by RIPC [85]. A meta-analysis by Zangrillo and colleagues reported that volatile anesthesia combined with RIPC reduced the post-operative mortality rate in patients undergoing cardiac surgery [86].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia is a confounder of cardioprotection by RIPC [205]. Interestingly, propofol anesthesia did not show significant differences in the primary outcome parameters including cardiovascular health, myocardial infarction, coronary revascularization, stroke and post-operative troponin I release in more than 90% of the CABG patients included in ERICCA trial [206].…”
Section: Challenges Of Translating Ripc In Clinical Settingsmentioning
confidence: 99%
“…Co-medication can also act as a confounder of RIPC. CABG patients receive medications such as anti-diabetic medicines, statins, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, morphine, calcium antagonists-which can interfere with the RIPC effect [205]. These medications may facilitate cardioprotection, which may obscure the potential of RIPC-mediated cardioprotection.…”
Section: Challenges Of Translating Ripc In Clinical Settingsmentioning
confidence: 99%
“…The type of anaesthesia was not standardized, which could interfere with RIPC. A recent meta‐analysis has shown that some types of anaesthesia may protect against ischaemia–reperfusion injury. The standard acute anaesthesia protocol in Denmark at all three participating centres during the study period consisted of a propofol and fentanyl‐based anaesthesia, sometimes supported with sevoflurane, at the discretion of the anaesthetist.…”
Section: Discussionmentioning
confidence: 99%